2015
DOI: 10.1002/2014tc003571
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-linear structure of the southern margin of Eurasia prior to the India-Asia collision: First paleomagnetic constraints from Upper Cretaceous volcanic rocks near the western syntaxis of Tibet

Abstract: We report the first combined geochronologic and paleomagnetic study of volcanic rocks from the Shiquanhe and Yare Basins at the westernmost Lhasa Terrane, which aims to provide an accurate constraint on the shape and paleoposition of the southern margin of Asia prior to the India-Asia collision. Three new 40 Ar/ 39 Ar ages of 92.5 ± 2.9 Ma, 92.4 ± 0.9 Ma, and 79.6 ± 0.7 Ma determined by fresh matrix or feldspar from lava flows suggest a Late Cretaceous age for the investigated units. Characteristic remanent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 73 publications
(173 reference statements)
0
45
1
Order By: Relevance
“…ID, paleopoles abbreviation; Fm, Formation; Gp, Group; volc, volcanics; Slat/Slon, latitude/longitude of the sampling area; Plat/Plon, latitude/longitude of the paleopole; A 95 , radius of the circle of 95% confidence; dp/dm, semiaxes of elliptical error of the pole at 95% confidence; Paleolat, the paleolatitudes of the eastern sector of the LT were calculated at an eastern reference point (29.3°N, 91.1°E); other paleolatitudes were calculated at a western reference point (31.7°N, 80.1°E); n / N , number of samples/sites used to calculate the Fisherian mean; F/R means a positive fold/reversal test; D means coexistence of dual polarity. References: 1, Tan et al (); 2, Sun et al (); 3, Cao et al (); 4, Huang et al (); 5, Chen et al (); 6, Chen et al (); 7, available data analyzed by van Hinsbergen et al (); 8, available data reanalyzed by Lippert et al (); 9, Liebke et al (); 10, Dupont‐Nivet et al (); 11, Chen et al (); 12, Yi et al (); 13, Ma et al (); 14, Chen et al (); 15, Yang, Ma, Zhang, et al ().…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ID, paleopoles abbreviation; Fm, Formation; Gp, Group; volc, volcanics; Slat/Slon, latitude/longitude of the sampling area; Plat/Plon, latitude/longitude of the paleopole; A 95 , radius of the circle of 95% confidence; dp/dm, semiaxes of elliptical error of the pole at 95% confidence; Paleolat, the paleolatitudes of the eastern sector of the LT were calculated at an eastern reference point (29.3°N, 91.1°E); other paleolatitudes were calculated at a western reference point (31.7°N, 80.1°E); n / N , number of samples/sites used to calculate the Fisherian mean; F/R means a positive fold/reversal test; D means coexistence of dual polarity. References: 1, Tan et al (); 2, Sun et al (); 3, Cao et al (); 4, Huang et al (); 5, Chen et al (); 6, Chen et al (); 7, available data analyzed by van Hinsbergen et al (); 8, available data reanalyzed by Lippert et al (); 9, Liebke et al (); 10, Dupont‐Nivet et al (); 11, Chen et al (); 12, Yi et al (); 13, Ma et al (); 14, Chen et al (); 15, Yang, Ma, Zhang, et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the precollisional southern margin of the LT at the early Cretaceous should have been located at a mean paleolatitude of ~18.8°N at ~117–132 Ma (Chen et al, ; Ma et al, ; Yang, Ma, Zhang, et al, ). For the far western part of the LT, only paleomagnetic results from Chen et al (), Yi et al (), and this study are available. Chen et al () reported Cretaceous paleomagnetic results of three limestone sites (22 specimens) from the LT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations